The Chemosensory Receptor Repertoire of a True Shark Is Dominated by a Single Olfactory Receptor Family. (12th January 2019) - Sharma, Kanika; Syed, Adnan S; Ferrando, Sara; Mazan, Sylvie; Korsching, Sigrun I
Abstract: Throughout the animal kingdom chemical senses are one of the primary means by which organisms make sense of their environment. To achieve perception of complex chemosensory stimuli large repertoires of olfactory and gustatory receptors are employed in bony vertebrates, which are characterized by high evolutionary dynamics in receptor repertoire size and composition. However, little is known about their evolution in earlier diverging vertebrates such as cartilaginous fish, which include sharks, skates, rays, and chimeras. Recently, the olfactory repertoire of a chimera, elephant shark, was found to be curiously reduced in odorant receptor number. Elephant sharks rely heavily on electroreception to localize prey; thus, it is unclear how representative their chemosensory receptor repertoire sizes would be for cartilaginous fishes in general. Here, we have mined the genome of a true shark, Scyliorhinus canicula (catshark) for olfactory and gustatory receptors, and have performed a thorough phylogenetic study to shed light on the evolution of chemosensory receptors in cartilaginous fish. We report the presence of several gustatory receptors of the TAS1R family in catshark and elephant shark, whereas TAS2R receptors are absent. The catshark olfactory repertoire is dominated by V2R receptors, with 5–8 receptors in the other three families (OR, ORA, TAAR). Species-specific expansions are mostly limited to the V2R family. Overall, the catshark chemosensory receptor repertoires are generally similar in size to those of elephant shark, if somewhat larger, showing similar evolutionary tendencies across over 400 Myr of separate evolution between catshark and elephant shark.